Bromine content of salts from DSDP Hole 13-134, Mediterranean Sea (Table 1) - Hsü, Kenneth J (Supplement to: Hsü, KJ (1974): The Miocene desiccation of the Mediterranean and its climatical and zoogeographical implications. Die Naturwissenschaften, 61(4), 137-142, https://doi.org/10.1007/BF00602586, 1974)
A deep-sea drilling cruise to the Mediterranean in late 1970 discovered the presence of an extensive evaporite deposit under the Mediterranean seabed. The deposit includes dolomite, anhydrite, gypsum, halite, and more soluble salts and covers an area more than 10**6 km 2. The origin of the evaporites has been interpreted as the product of desiccation, when the Mediterranean was isolated from the Atlantic during the Late Miocene Messinian stage, 5-7 million years ago. The desiccation led to a total destruction of pre-Messinian marine faunas and permitted the development of oligohaline and euryhaline faunas in the Mediterranean region. The circum-Mediterranean lands became arid and forests were replaced by savannas and steppes. Large-scale migrations, especially of grazing animals, may have been the consequence of such a drastic change in geography and in ecology.